A method for diagnosing the implosion symmetry in inertial confinement fusion with wide-angle VISAR - Wu Yuji; Guan Zanyang; Zhang Qing; Jing Longfei; Ren Kuan; Liang Juxi; Chen Xudan; Li Yulong; Wang Feng (Nuclear Fusion)
A method for diagnosing implosion symmetry in inertial confinement fusion (ICF) with wide-angle velocity interferometer system for any reflector (VISAR)was proposed in this study. The method considers the object-image relationship of the wide-angle VISAR, characteristics of the fringe pattern, and the symmetry theory; the fringe pattern must be continuous in space to apply this method. Hydrodynamic calculations showed that the radiation-temperature distribution on the surface of capsule was spatially continuous, indirectly proving the applicability of the method. The evolution of P2 asymmetry at different positions of the capsule was examined through an eight-beam laser indirect-drive experiment at a 10 kJ-level laser facility, proving the feasibility of the method. The application of wide-angle VISAR for the diagnosis of implosion symmetry in ICF was more accurate and intuitive and demonstrated high spatiotemporal resolution and wide detection range. This method can provide reference data for the micro-mechanism study of hydrodynamic instability and radiation-driven asymmetry, as well as support for optimizing the implosion compression process to achieve efficient and stable ignition.